Optimizing English Language Learning at the BIF Foundation Special Needs School through the Merdeka Curriculum - Rinda, Rinda (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
The implementation of the Merdeka Curriculum has introduced greater flexibility and autonomy in instructional practices, including in special education contexts. This study aims to examine how the Merdeka Curriculum is implemented in English language instruction at Sekolah Luar Biasa (SLB) under the Bina Insani Firaas Foundation in Mojokerto, East Java. Using a qualitative descriptive research design, data were collected through semi-structured interviews, classroom observations, and document analysis involving English teachers, school principals, and a foundation leader. The findings indicate that curriculum flexibility enables teachers to adapt English instruction to students’ diverse learning needs by simplifying materials, adjusting learning pace, and employing visual, multimodal, and experiential teaching strategies. These practices support student engagement, participation, and confidence in English learning activities. However, the study also identifies challenges related to limited inclusive learning materials, insufficient access to assistive technology, and a lack of targeted professional development for English teachers in SLB settings. Institutional support and teacher collaboration emerge as important factors that facilitate the implementation of inclusive English language instruction. This study highlights that the Merdeka Curriculum holds strong potential to support inclusive English language teaching when accompanied by adequate resources, professional support, and collaborative efforts among educational stakeholders. The findings contribute empirical insights into curriculum implementation in special education contexts and offer practical implications for the development of inclusive English language teaching practices.